Age at Primary Cleft Lip Repair: A Potential Bellwether Indicator for Pediatric Surgery. Issue 6 (24th June 2021) - Vanderburg, Richard; Alonso, Nivaldo; Desai, Priya; Donkor, Peter; Mossey, Peter; Stieber, Erin; V. Mehendale, Felicity
Abstract : Background: The bellwether procedures described by the Lancet Commission on Global Surgery represent the ability to deliver adult surgical services after there is a clear and easily made diagnosis. There is a need for pediatric surgery bellwether indicators. A pediatric bellwether indicator would ideally be a routinely performed procedure, for a relatively common condition that, in itself, is rarely lethal at birth, but that should ideally be treated with surgery by a standard age. Additionally, the condition should be easy to diagnose, to minimize the confounding effects of delays or failures in diagnosis. In this study, we propose the age at primary cleft lip (CL) repair as a bellwether indicator for pediatric surgery. Method: We reviewed the surgical records of 71, 346 primary cleft surgery patients and ultimately studied age at CL repair in 40, 179 patients from 73 countries, treated by Smile Train partners for 2019. Data from Smile Train's database were correlated with World Bank and WHO indicators. Results: Countries with a higher average age at CL repair (delayed access to surgery) had higher maternal, infant, and child mortality rates as well as a greater risk of catastrophic health expenditure for surgery. There was also a negative correlation between delayed CL repair and specialist surgical workforce numbers, life expectancy, percentage of deliveries by C-section, total health expenditure per capita, and Lancet Commission on Global Surgery procedure rates. Conclusion: These findings suggest that age at CL repair has potential to serve as a bellwether indicator for pediatric surgical capacity in Lower- and Middle-income Countries.